2017
DOI: 10.1002/aelm.201700375
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Backbone Fluorination on the Dielectric Constant of Conjugated Polythiophenes

Abstract: The ability to modify or enhance the dielectric constant of semiconducting polymers can prove valuable for a range of optoelectronic and microelectronic applications. In the case of organic photovoltaics, increasing the dielectric constant of the active layer has often been suggested as a method to control charge generation, recombination dynamics, and ultimately, the power conversion efficiencies. In this contribution, the impact that the degree and pattern of fluorination has on the dielectric constant of po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(44 citation statements)
references
References 52 publications
(62 reference statements)
1
43
0
Order By: Relevance
“…The values of α for the P113‐ and P114‐based PSCs are about 0.934 and 0.961, respectively. The higher value of α for the PSCs based on P114 indicates suppression of bimolecular recombination under short‐circuit conditions, as is consistent with more balanced charge transport in the active layer based on P114 to avoid bimolecular recombination . The variation of V oc with P in is evaluated by the expression V oc ∝ ( nkT / q )ln ( P in ), where n is the slope of the plot of V oc versus P in .…”
Section: Resultsmentioning
confidence: 62%
“…The values of α for the P113‐ and P114‐based PSCs are about 0.934 and 0.961, respectively. The higher value of α for the PSCs based on P114 indicates suppression of bimolecular recombination under short‐circuit conditions, as is consistent with more balanced charge transport in the active layer based on P114 to avoid bimolecular recombination . The variation of V oc with P in is evaluated by the expression V oc ∝ ( nkT / q )ln ( P in ), where n is the slope of the plot of V oc versus P in .…”
Section: Resultsmentioning
confidence: 62%
“…[35] The kinetic Monte Carlo (kMC) method is a powerful simulation technique to model the time-dependent behavior of physical systems. [11,12,[51][52][53][54][55][56][57][58][59][60] In addition, pristine organic materials with low energetic disorder support separation dynamics: a low disorder leads to a more ballistic transport and more efficient separation. [36] A specific advantage of the kMC method is that it allows to include explicit particle-particle interactions and that it gives direct access to the charge trajectories which can be used to assess the CP displacement from the heterojunction.…”
Section: Wwwadvtheorysimulcommentioning
confidence: 99%
“…The compatibility of polymers to large-area (e.g., roll-to-roll) manufacturing processes on flexible substrates [6,7] enables low-cost fabrication and opens up numerous novel fields of application. The ability to tune the optical and electrical properties of polymers, for example, the bandgap [8][9][10] or the response to electric fields (i.e., the dielectric permittivity ε), [11,12] by chemical engineering allows to adapt organic semiconductors to the desired needs. Specifically, organic photovoltaic cells have been intensely studied during the past decade [13][14][15] and power conversion efficiencies (PCEs) of DOI: 10.1002/adts.201800032 pioneering devices exceed 13% [16][17][18] by now.…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that increasing ɛ r can reduce the exciton binding energy and lead to more efficient exciton dissociation, thereby enhancing the shortcircuit current density (J SC ) and PCE of OSCs. [18][19][20][21][22] Polymers comprising alternating conjugated electron donor (D) and acceptor (A) building blocks on the backbone (Type I in Figure 1) have been widely investigated as donors for OSCs due to their enhanced hole mobilities and tunable energy levels. [23][24][25][26] More importantly, the D-A structure polarizes the polymer or increases the dielectric constant, which would help reduce the exciton binding energy.…”
Section: Introductionmentioning
confidence: 99%